1992
DOI: 10.1093/nar/20.12.3191
|View full text |Cite
|
Sign up to set email alerts
|

Intron requirement for expression of the human purine nucleoside phosphorylase gene

Abstract: Abbreviated purine nucleoside phosphorylase (PNP) genes were engineered to determine the effect of introns on human PNP gene expression. PNP minigenes containing the first intron (complete or shortened from 2.9 kb down to 855 bp), the first two introns or all five PNP introns resulted in substantial human PNP isozyme expression after transient transfection of murine NIH 3T3 cells. Low level human PNP activity was observed after transfection with a PNP minigene containing the last three introns. An intronless P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 58 publications
2
54
1
Order By: Relevance
“…In addition, repeats in first introns were associated with greater expression divergence than repeats in other introns. This observation is consistent with previous work showing that most intronic regulatory regions occur in the first intron (Rohrer and Conley 1998), that the first intron has the highest divergence between human and chimpanzees (Gazave et al 2007), and that the first intron influences gene expression more than other introns (Jonsson et al 1992;Charron et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, repeats in first introns were associated with greater expression divergence than repeats in other introns. This observation is consistent with previous work showing that most intronic regulatory regions occur in the first intron (Rohrer and Conley 1998), that the first intron has the highest divergence between human and chimpanzees (Gazave et al 2007), and that the first intron influences gene expression more than other introns (Jonsson et al 1992;Charron et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In many species intron 1 length seems to be positively regulated with the expression level of the respective gene. 21,[24][25][26][27][28][29] Furthermore, neuronal genes and genes that are involved in development seem to have a higher content of non-coding DNA, which might assist in the tight regulation of their expression. 17 In plants, the propensity of these elements to influence gene expression was termed intron-mediated enhancement.…”
Section: Architecture Of the Huntingtin Gene And Its Influence On Splmentioning
confidence: 99%
“…Previous efforts to examine the effect of mRNA splicing on the level of gene expression have demonstrated that a number of intron containing genes, including the genes encoding ␤-globin, thymidylate synthase, or purine nucleoside phosphorylase, are very poorly expressed when transcribed as cDNAs but effectively expressed if one or more introns are present in cis (Buchman and Berg 1988;Deng et al 1989;Ryu and Mertz 1989;Jonsson et al 1992). On the other hand, cDNAs derived from some other intron containing genes have been reported to express at high levels in cultured cells even in the absence of any introns (Pasleau et al 1987;Brinster et al 1988;Malim et al 1988).…”
Section: Introductionmentioning
confidence: 99%